KEBIJAKAN MUTASI JABATAN STRUKTURAL DI LINGKUP PEMERINTAHAN KABUPATEN KEPULAUAN SANGIHE - Bataha, Katerina (JURNAL ADMINISTRASI PUBLIK, 2013)
ABSTRACT : Mutations structural position is one way that can be done to improve public services. Mutations as well as the incarnation or embodiment of the organizational dynamics that serve as one way to achieve organizational goals and implemented to reduce the tedium of the work, increase knowledge, skills and increase motivation and morale, in addition to placing appropriate officials with expertise in the areas of their each.Issues to be addressed in this study is how the policy positions of structural mutations in the scope of the Sangihe regency government .This study uses qualitative methods. This study aims to describe, analyze and determine the impact of structural policies mutation positions in the public service with the indicators work experience, knowledge and skills as well as utilization of employees.Results of research conducted by gathering the data obtained through interviews observasidan are : ( 1 ) Work experience of maturity seen an employee who has been carrying out work in a specified period, (2 ) knowledge and skills acquired structural due to mutation, (3 ) Utilization employees through structural mutation positions to maximize employee who simply work quietly in one place only.Based on the results of the study conclude that mutations in the structural position goes normative Sangihe regency, conducted for the benefit of the organization or public service better. Policy and structural position mutations impact both on public services. Based on the conclusion of the study, it is suggested, the government made a clump positions and monitor the working climate in the scope of local government so that there is a valid handle and facilitate the implementation of the structural position mutations.Keywords : Policy, mutation,, structural position